The Global network of regional sustainable energy centres : a post-2015 South-South and triangular partnership - powering the path to inclusive and sustainable industrial development and SE4ALL.
Features the set of global networks of regional sustainable energy centres in Africa, the Caribbean, the Pacific and the Arab region, coordinated by the Energy and Climate Change Branch of UNIDO.
Keywords: ENERGY EFFICIENCY